2018
DOI: 10.1016/j.apergo.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic evaluation of pilot oxygen mask designs

Abstract: A revised pilot oxygen mask design was developed for better fit to the Korean Air Force pilots' faces. The present study compared an existing pilot oxygen mask and a prototype of the revised mask design with 88 Korean Air Force pilots in terms of subjective discomfort, facial contact pressure, and slip distance on the face in high gravity. The average discomfort levels, facial contact pressures, and slip distance of the revised mask were reduced by 33%-56%, 11%-33%, and 24%, respectively, compared to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The revised oxygen masks developed in the present study showed a better fit than the existing masks by a usability evaluation in our follow-up study [36]. The prototypes of the revised designs of four sizes were manufactured using materials similar to the existing MBU-20/P and compared to the existing designs by 88 KAF pilots in terms of discomfort, facial contact pressure, and performance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The revised oxygen masks developed in the present study showed a better fit than the existing masks by a usability evaluation in our follow-up study [36]. The prototypes of the revised designs of four sizes were manufactured using materials similar to the existing MBU-20/P and compared to the existing designs by 88 KAF pilots in terms of discomfort, facial contact pressure, and performance.…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, the ergonomic designs of mask boundary could be found through the iterative virtual fit analysis method before prototyping. In our follow-up study, the prototype of the revised oxygen mask of the medium-wide size was fabricated first and found satisfactory to KAF pilots in terms of fit and comfort and minor design issues of the prototype (e.g., shape and thickness of flap) were reported as those to be improved; the prototypes of the other three sizes were fabricated and found satisfactory by KAF pilots [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The displacement in this study means a pushed-in distance of the skin surface caused by the positioning of the spline curvature toward the face. But, the position of the spline curvature was somewhat artificial and might not be very realistic, although the resulted contact pressure values were quite reasonable compare to the previous study [23,24]. The more realistic way of fitting the spline curvature to the faces needs to be studied.…”
Section: Discussionmentioning
confidence: 89%
“…As our previous research, the virtual fit analysis method [1,2,22] was proposed, which assessed the fit of an oxygen mask design (which was defined as spline curvature, either) onto 3D human faces by calculating Euclidean distances between the mask and facial surface. In the virtual fit analysis method, any material properties of both the face and mask were not considered; however, the prototype of the new oxygen mask designed based on the virtual fit analysis showed good fit and comfort compared to the existing one [23]. That was because not only a few facial dimensions but also the numerous facial shapes could be considered when the new design was found.…”
Section: Discussionmentioning
confidence: 99%
“…In headwear, a good fit is often required in order for the product to function properly. This is especially important in protective gear or medical products as the fit of these products could have a direct impact on the wearer's health and safety [1][2][3][4]. Thus, anthropometric information of the head and face is necessary to describe the variation in size and shape in order to develop a product that fits the user.…”
Section: Introductionmentioning
confidence: 99%